Match-Referee Matching Model in Football - Celik, Onur Burak (International Journal of Contemporary Economics and Administrative Sciences, 2021)
Referees are assigned to football matches in Turkey by a three-person subcommittee formed by Central Referee Committee, a subsidiary of the Turkish Football Federation, in a non-transparent way and this procedure makes manipulation possible. Therefore, referee appointments are among the topics discussed in the football world. It is a major deficiency that the matching theory, which has been successful in regulating many problematic markets, has not been used to date in football for referee appointments. In this study, a match-referee matching model, using the Gale-Shapley algorithm, for the football matches played in Turkish professional football leagues is proposed. The match-referee matching result offered by this algorithm is the best possible stable matching result for the clubs. This matching result is produced in line with the preferences of the clubs and clubs' satisfaction is at the forefront. Most importantly, it is obtained through a transparent, clear, fair and manipulation-free match-referee matching system.